Method of Plasty of the Lateral Wall of the Maxillary Sins in Sinus Lifting (Eurasian Research Bulletin, 2023)
The study involved 18 patients with defects in the dentition and severe atrophy of the bone tissue of the upper jaws in the distal sections. For plasty of the lateral window of the maxillary sinus after sinus lift, a brefoxeno graft from the bone tissue of newborn lambs was prepared. The preoperative X-ray examination included CBCT, which made it possible to determine not only the geometric and density parameters of the bone tissue of the alveolar process and VChS, but also the condition of the sinus mucosa. The preserved xenobone was modeled with surgical scissors to a size that covered the window in the lateral wall of the maxillary sinus. According to micrographs, during densitometry, the restoration of bone tissue fibers was assessed. Analysis and comparison of micrograph data on the 30th, 90th and 180th days after the operation showed signs of bone tissue regeneration in the defect zone, which is confirmed by an increase in mineral density (by 0.193; 0.099; 0.086 g/cm3).